Enhancing agricultural productivity of CLMV countries: Challenges and agenda for reforms - Aladdin D. Rillo; Mercedita A. Sombilla (Asian Development Bank Institute (ADBI), 2015)
Responding positively to economic reforms, the economies of Cambodia, the Lao People's Democratic Republic, Myanmar, and Viet Nam (CLMV) have shown tremendous growth since the mid-1980s, including in their respective agriculture sectors. Recent developments, however, have brought into question the CLMV countries' ability to sustain further increases in agricultural productivity given the slow pace of reforms and emerging challenges. Going forward, the reform agenda must go beyond the traditional view of expanding yields and supply of agricultural products for development gains in the sector to contribute to inclusive growth, poverty alleviation, and food security. This will require changing the market structures and regulatory policies that govern the sector.
Keywords: Q1; Q21; Q28; 330; agricultural productivity; clmv; agriculture policy